2000
DOI: 10.1093/jhered/91.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication. The Rift Valley complex as a barrier to gene flow for Anopheles gambiae in Kenya: the mtDNA perspective

Abstract: Descriptions of A. gambiae population structure based on microsatellite loci and mitochondrial DNA (mtDNA) were incongruent. High differentiation of populations was measured across the Rift Valley by microsatellites, but no differentiation was detected based on mtDNA. To resolve this conflict, we compared the old data to new mtDNA data using the same specimen previously genotyped in microsatellite loci. Analysis of a larger number of mtDNA sequences resulted in high and significant differentiation between popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…By analogy with An. gambiae (Lehmann et al, 2000), the lack of unique alleles and the higher F ST than Rho ST values among northeastern populations of P. perniciosus both suggest that pure drift was the main differentiating process for the northeastern region of Spain. This is consistent with the hypothesis of historical migration from a southern Ice Age refuge, with the northeastern population arising as a northern peripheral isolate in which founder effects and bottleneck events led to the loss of rare alleles and significant changes in allele frequencies, as argued for temperate European insects (Hewitt, 1996(Hewitt, , 1999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By analogy with An. gambiae (Lehmann et al, 2000), the lack of unique alleles and the higher F ST than Rho ST values among northeastern populations of P. perniciosus both suggest that pure drift was the main differentiating process for the northeastern region of Spain. This is consistent with the hypothesis of historical migration from a southern Ice Age refuge, with the northeastern population arising as a northern peripheral isolate in which founder effects and bottleneck events led to the loss of rare alleles and significant changes in allele frequencies, as argued for temperate European insects (Hewitt, 1996(Hewitt, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies of insect transmitters of disease are potentially important for planning intervention strategies, as they can help predict the dispersal not only of vectorial traits associated with specific populations but also of genetically modified organisms and the genes they carry. The interest of this approach has been demonstrated for the Anopheles gambiae complex, which contains most of the major vectors of human malaria in sub-Saharan Africa (Lehmann et al, 1996(Lehmann et al, , 2000Donnelly and Townson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…arabiensis in Kenya have implications on the population genetic structure of anopheline mosquitoes. Lehmann et al (1999Lehmann et al ( , 2000 demonstrated that An. gambiae populations from western Kenya were highly differentiated genetically from Kenyan coastal populations, suggesting that the Great Rift Valley plays an important role in limiting An.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, significant isolation between coastal and savannah An. gambiae populations from Kenya, 700 km away, has been recorded (McLain et al, 1989;Kamau et al, 1999;Lehmann et al, 1999Lehmann et al, , 2000. These populations are separated by the eastern arm of the Rift valley complex.…”
Section: Discussionmentioning
confidence: 99%